Comparison between the Effect of Aflibercept (Eylea) and Ranibizumab (Lucentis) on Intraocular Pressure after 3rd Injection in Treatment of Diabetic Macular Edema - Hossam El Deen Khalil; Ahmed Gouda; Ibrahim Abd Allah (Egyptian Journal of Medical Research, 2022)
Background: Currently, intravitreal injection of anti-VEGF is typically applied in the treatment of choroidal neovascularization (CNV), which occurs in patients with wet age-related macular degeneration (wAMD) and high myopia. It is also used to treat patients with macular edema secondary to diabetic retinopathy (DME) and retinal vein occlusions (RVO-ME). Objectives: This is a prospective, comparative clinical study between aflibercept (Eylea) and Ranibizumab (Lucentis) done to evaluate changes in intraocular pressure following 3rd intravitreal injection of different types of anti-VEGF agents used in patients presenting with proliferative diabetic retinopathy and diabetic macular edema and determine the need to monitor IOP after intravitreal injections of anti-VEGF agents. Patients and Methods: This is a prospective, comparative clinical study, that was conducted on 60 eyes of 60 patients. Patients scheduled for intravitreal injection of anti-VEGF 3 times were randomly divided into 2 groups: Group A: 30 eyes will be scheduled for intravitreal injection of ranibizumab (0.5 mg/0.05 ml) 3 times for the treatment of diabetic macular edema or proliferative diabetic retinopathy. Their mean age was (59.80±7.27 years), Group B: 30 eyes will be scheduled for intravitreal injection of aflibercept (2 mg/0.05 ml) 3 times for the treatment of diabetic macular edema or proliferative diabetic retinopathy. Their mean age was (59.83±6.29 years). Results: There is no significant difference between IOP after 1 week,1 month and 2 months regarding ranibizumab and aflipercept, however, the range of decrease of IOP after one month regarding aflipercept was less than that of ranibizumab, accordingly, we can correlate this difference to the longer half life of aflipercept than that of ranibizumab. Conclusion: The current study confirms the results of previous studies which showed the safety of multiple IV injection of anti-VEGF agents for IOP elevation in post-injection first month in non glaucomatous patients. However, there might be a tendency to  increased IOP in glaucoma cases and repeated injections, so further studies about safety of repeated injections, in glaucomatous patients and for different retinal disorders should be carried out. Our study for intravitreal injections recommend “monitoring of IOP after injection and providing therapy when elevated IOP warrants intervention”.